CEST imaging of the APT and ssMT predict the overall survival of patients with glioma at the first follow-up after completion of radiotherapy at 3T - Knebel Doeberitz, Nikolaus von; Kroh, Florian; Breitling, Johannes; König, Laila; Maksimovic, Srdjan; Grass, Svenja; Adeberg, Sebastian; Scherer, Moritz; Unterberg, Andreas; Bendszus, Martin; Wick, Wolfgang; Bachert, Peter; et al. (Radiotherapy and oncology, 2023)
Outcome prediction of patients with glioma early after the completion of radiotherapy represents a major clinical challenge. Previously, the prognostic value of chemical exchange saturation transfer (CEST) imaging has been demonstrated in patients with newly diagnosed glioma. The objective of this study was to assess the potential of amide proton transfer (APT)-, relayed nuclear Overhauser effect (rNOE)- and semi-solid magnetization transfer (ssMT)-imaging according to Zhou et al. (APTwasym), Goerke et al. (MTRRexAPT, MTRRexNOE and MTRRexMT) and Mehrabian et al. (PeakAreaAPT, PeakAreaNOE and MTconst) for the prognostication of the overall survival (OS) of patients with glioma at the first follow-up after the completion of radiotherapy.